Implementing Tax Coordination and Harmonization through Voluntary Commitment - Grégoire Rota-Graziosi (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
Pareto-improving tax coordination, and even tax harmonization, are Nash implementable between sovereign countries without any supranational tax authorities. Following Schelling's approach, we consider voluntary commitment, which constrains countries' respective tax rate choices. We develop a commitment game where countries choose their strategy sets in preliminary stages and play consistently during the final one. We determine the set of tax rates, which are implementable by commitment. This allows countries to reach Pareto-improving equilibriums. We also establish that complete tax harmonization may emerge as the subgame perfect Nash equilibrium of the commitment game as long as the asymmetry between countries remains limited. Our analysis contributes to the rationale of tax ranges and, more broadly, of non binding but self-enforcing commitments (not equivalent to cheap talk) in the context of tax competition.
Keywords: H30; H86; C72; 330; Tax competition; tax coordination; commitment